Computer‐Aided Designed and 3‐Dimensionally Printed Porous Tissue Bioscaffolds for Craniofacial Soft‐Tissue Reconstruction. (23rd August 2013) - Zopf, David A.; Mitsak, Annie; Flanagan, Colleen L.; Maki, Aaron; Wheeler, Matthew; Green, Glenn E.; Hollister, Scott J.
Abstract : Objectives: Introduce our groups' innovative processes using image‐based design and several 3‐dimensionally printed scaffolds for head and neck cartilaginous reconstruction. Applications for auricular reconstruction and nasal reconstruction are discussed. Study Design: Proof of concept revealing novel methods for bioscaffold production with in vitro and in vivo data demonstrating preliminary scaffold behavior. Methods: DICOM computed tomography (CT) images undergo segmentation and image‐based Boolean design. Three‐dimensional (3D) designed, bioresorbable, poly‐L‐caprolactone scaffolds are printed. Subcutaneous in vivo implantation of auricular and nasal scaffolds was performed in a porcine model. Auricular scaffolds were seeded with primary porcine auricular chondrocytes in a hyaluronic acid/collagen hydrogel, and cultured in a prochondrogenic bioreactor environment. Results: Auricular and nasal constructs with several micropore architectures are rapidly manufactured with high fidelity anatomic appearance. Subcutaneous in vivo implantation of auricular and nasal scaffolds resulted in excellent appearance. Histologic analysis demonstrated cartilaginous growth within and respecting the boundaries of the scaffold. Cartilage growth was not seen outside of the scaffold, potentially suggesting a prochondrogenic effect of the scaffold or prevention of chondrocyte dedifferentiation. Conclusions: Image‐based design processes and 3D printing in the production of cartilaginous structures for several challenging reconstructive applications is introduced. Bioscaffolds may allow regeneration of soft tissue structures that are replaced with native extracellular matrix.